Cholinergic Inhibition of Ventral Midbrain Dopamine Neurons - Fiorillo, Christopher D. (J Neurosci, 2000)
Muscarinic acetylcholine receptors are common throughout the CNS. The predominant subtypes in the brain are positively coupled to phosphoinositide hydrolysis and have been found to modulate multiple conductances. Muscarinic receptor activation is most often observed to be excitatory because of suppression of various potassium conductances. Here it is reported that three distinct effects of muscarinic receptor activation can be observed in isolation from one another, depending on the duration of receptor activation and the concentration of agonist. Brief activation of muscarinic receptors, as is likely to occur with normal synaptic transmission, hyperpolarized dopamine neurons of the ventral midbrain through a calcium-activated potassium conductance. With repeated or persistent activation of muscarinic receptors, the hyperpolarizing response was entirely desensitized in the absence of any change in resting membrane potential. With sustained activation by higher concentrations of agonist, dopamine neurons were depolarized. This demonstrates that muscarinic receptors can mediate very diverse, and even opposing, postsynaptic effects on neurons depending on the pattern of acetylcholine release.